T-cell virtuosity in ‘‘knowing thyself” - Acuto, Oreste (Frontiers in Immunology, 2024)
Major Histocompatibility Complex (MHC) I and II and  T-cell antigen receptor (TCR) govern fundamental traits of adaptive immunity. They form a membrane-borne ligand-receptor system weighing host proteome integrity to detect contamination by nonself proteins. MHC-I and -II exhibit the "MHC-fold" able to bind a large assortment of short peptides as proxies for self and nonself proteins. The ensuing varying surfaces are mandatory ligands for Ig-like TCR highly mutable binding sites. Conserved molecular signatures guide TCR ligand binding sites to focus on the MHCfold (MHC-restriction) while leaving many opportunities for its most hypervariable determinants to contact the peptide. This riveting molecular strategy affords many options for binding energy compatible with specific recognition and signalling, aimed to eradicate microbial pathogens and cancer cells. While the molecular foundations of  T-cell adaptive immunity are largely understood, uncertainty persists on how peptide-MHC binding induces TCR signals that instruct cell-fate decisions. Solving this mystery is another milestone for understanding  T-cells' self/nonself discrimination. Recent developments revealing innermost links between TCR structural dynamics and signalling modality should help dissipating this long sought-after enigma.